Pengaruh Lingkungan Kerja Terhadap Kepuasan Karyawan Dan Implementasinya Terhadap Kinerja Karyawan Pada PT. PLN ( Persero ) UPDK Mahakam Samarinda - Armini Ningsih; Syachrul Syachrul; Tia Ratnasari (Politeknik Negeri Samarinda, 2020)
The Effect of Work Environment on Job Satisfaction and Its Implications on Employee Performance at PT PLN (Persero) UPDK Mahakam This research aims were to determine the effect of work environment on job satisfaction and its impact on employee performance at PT PLN (Persero) UPDK Mahakam. With the subject of this study were all employees of PT PLN (Persero) UPDK Mahakam with a total of 40 people. Data collection used in this research was a questionnaire that has been tested for validity and reliability while data analysis was done using multiple linear regression analysis. with Path Analysis tools using Smart PLS, and SPSS. The results showed that: 1) Work Environment Variable (X1) had a significant effect on Job Satisfaction (Y1) at PT PLN (Persero) UPDK Mahakam, 2) Work Environment Variables (X1) insignificant effect on Employee Performance (Y2) at PT PLN (Persero) UPDK Mahakam, 3) Job Satisfaction Variable (Y1) significantly influenced the Employee Performance (Y2) at PT PLN (Persero) UPDK Mahakam.